Transactional hazards, institutional change, and capabilities: Integrating the theories of the firm - Brahm, Francisco; Tarziján, Jorge (Strategic Management Journal, 2014)
Using a detailed dataset from the Chilean construction industry, we explore how the predictions of the transaction cost and capabilities theories interact to explain building contractors' decisions to ‘make or buy’ the specialty trade activities needed to complete a construction project. We show that the contractor's productive capabilities strongly mediate the relationship between transaction hazards that originate from either temporal specificity or an exogenous change in the subcontracting law and the vertical integration decision. The inclusion of differential capabilities and its interaction with transactional hazards infuse contractors' boundary choices with systematic patterns of heterogeneity and contribute to the integration of these theoretical perspectives. Our analysis corrects for the endogeneity of the capabilities variable and provides a detailed assessment of the marginal effects in logit models . Copyright © 2013 John Wiley & Sons, Ltd.